2008
DOI: 10.1002/smi.1190
|View full text |Cite
|
Sign up to set email alerts
|

Sweating the small stuff: how different types of hassles result in the experience of stress

Abstract: Summary The current study examines the level of stress caused by different types of daily hassles. Using an open-ended response format, participants (n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…As expected, minor life events were more prominent than major ones among college students, and previous studies demonstrated that stress from minor life events among the ordinary were significantly more important in affecting distress compared with the major events. 41,42 Our findings also suggested that the 3 virtues play a different function in the stress-outcome equation.…”
Section: Test Of Mediation Modelmentioning
confidence: 72%
“…As expected, minor life events were more prominent than major ones among college students, and previous studies demonstrated that stress from minor life events among the ordinary were significantly more important in affecting distress compared with the major events. 41,42 Our findings also suggested that the 3 virtues play a different function in the stress-outcome equation.…”
Section: Test Of Mediation Modelmentioning
confidence: 72%
“…Studies appear to consistently show that females report more chronic stressors related to interpersonal relationships (e.g., friends, relatives, acquaintances in social network) than males (Barker, 2007; Davis, Matthews, & Twamley, 1999; Liu & Alloy, 2010; McIntyre, Korn, & Matsuo, 2008; Shih, Eberhart, Hammen, & Brennan, 2006). A few studies have demonstrated that males experience more work-related and financial chronic stressors than women (Loosemore & Waters, 2004; Young & Korszun, 2010).…”
Section: Gender As a Moderator Of Physiological Responses To Stressmentioning
confidence: 99%
“…Daily hassles are the minor, frequently occurring challenges of daily life, such as household chores or having a disagreement with a family member (Almeida, 2005;Bolger, Delongis, Kessler, & Schilling, 1989;McIntyre, 2008) that have immediate, direct effects on health and well-being (Bolger, Davis, & Rafaeli, 2003). The chronic experience of stress, such as that which may occur in response to continued daily stress within the context of widowhood may lead to increased proinflammatory cytokines (Kiecolt-Glaser, McGuire, Robles, & Glaser, 2002) and an overactivation and dysregulation of the body's stress response that may result in a decreased ability to respond to stress and potentially negative health outcomes (Finch & Seeman, 1999).…”
mentioning
confidence: 99%